2015
DOI: 10.1108/lhs-12-2013-0045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of service attributes on customer satisfaction and loyalty in a healthcare context

Abstract: The study shows that customer perceptions at the service attribute level can often be the key to the generation and management of customer satisfaction and loyalty. It also has significance for how satisfaction and loyalty with HPs can be improved in a hospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…Therefore, organizations must ensure improvement in their customer servicing skills in order to meet customer's needs and wants. Similarly, Lonial and Raju (2015) examined the role of perceived service attributes in determine the overall customer satisfaction and loyalty for health-care sector. Their findings showed that organizations can prosper by identifying and focusing on serious attributes as part of their customer relationship management plan so as to attain customer satisfaction.…”
Section: Research Framework Empirical Studiesmentioning
confidence: 99%
“…Therefore, organizations must ensure improvement in their customer servicing skills in order to meet customer's needs and wants. Similarly, Lonial and Raju (2015) examined the role of perceived service attributes in determine the overall customer satisfaction and loyalty for health-care sector. Their findings showed that organizations can prosper by identifying and focusing on serious attributes as part of their customer relationship management plan so as to attain customer satisfaction.…”
Section: Research Framework Empirical Studiesmentioning
confidence: 99%
“…Only a handful of studies have examined these “off pattern” segments. A recent exception is Lonial and Raju (2015)’s analysis of the customer base of a healthcare service provider. These researchers examined high satisfaction versus low satisfaction groups, and, separately, low and high loyalty groups and found that although one of the service attributes played a role in both satisfaction and loyalty, other service attributes that drove satisfaction were different from those that drove loyalty.…”
Section: Research Progress Since Thenmentioning
confidence: 99%
“…auto-repair, education, finance and banking, gyms, health care, hotels, spas, wireless, B2b, etc. (Lee et al , 2001; Lonial and Raju, 2015; Yüncü, 2015), the contrast between industry types as a contingency factor is seriously underexplored (Dagger and David, 2012, and Pollack, 2009 being comforting exceptions). Specifically, the contextual contrast covered in our study, namely, high versus low contact is not examined in any of the studies, and likewise, the differential roles of technical versus functional qualities have not been addressed.…”
Section: Research Progress Since Thenmentioning
confidence: 99%
“…The positive link between RQ's satisfaction and trust with WOM are also in line with previous studies like Henning-Thurau et al (2002), Chen et al (2008), Satta et al (2015), and Su et al (2014) for satisfaction; while Guenzi and Georges (2010), Chen et al (2008), Baloglu et al (2014), and Su et al (2014) for trust. In addition, the positive link between RQ's satisfaction and trust with SOP are also similar to Lin and Ding (2005), Caceres and Paparoidamis (2007), Shamdasani and Balakrishnan (2000), Rauyruen and Miller (2007), Chen et al (2008), Lonial and Raju (2015), and Kim, Lee, and Suh (2015) for satisfaction; while Guenzi and Georges (2010), Chen et al (2008), Lin and Ding (2005), Shamdasani and Balakrishnan (2000), Azam (2015), Bowden-Everson et al (2013), Butt and Aftab (2013) and Aldas-Manzano et al (2011) for trust.…”
Section: Discussionmentioning
confidence: 66%